GENETICA DA AQUIROPODIA ('THE HANDLESS AND FOOTLESS FAMILIES OF BRAZIL') II: AQUIRIA E CASOS 'SIMILARES' A AQUIROPODIA - Freiere Maia, A. (My University, 1974)
Acheiropodia is a congenital malformation with well defined characteristics and well established genetic etiology. It is proposed that the expression 'acheiropodia' be restricted exclusively to such cases and others that follow the definition. Several examples are given which do not agree with the concept; therefore, they should not be confounded with cases of acheiropodia. By analogy with what happens in acheiropodia, it is proposed that the expression 'acheiria' be restricted to those cases where the anomaly affects only the upper limbs and follows the same typical pattern of acheiropodia. A family analysis of one such case is mentioned, but there is not sufficient information to test the hypothesis of a simple genetic mechanism.
Genetics of acheiropodia (the handless and footless families of Brazil). II: Acheiria and cases 'similar' to acheiropodia